Выбор полупроводникового материала для детекторов гамма-излучения - Abyzov, A. S.; Azhazha, V. M.; Davydov, L. N.; Kovtun, G. P.; Kutny, V. E.; Rybka, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
Among the semiconductors used in spectrometers and dosimeters, wide-bandgap compounds such asCd1-xZnxTe, CdTe, and HgI2 occupy leading positions. The question arises as to whether this choice is definitive and optimal. In an attempt to answer this question, physical parameters critical to the detector’s sensitivity were selected. These include, first and foremost, mobility, lifetime, atomic number, and resistivity. Based on the selected parameters, an analysis of binary compounds with a tetrahedral structure was conducted.